BUSINESS AND REGIONAL MODELS FOR THE APPLICATION OF THE CIRCULAR ECONOMY - T. Turlakova (Trakia Journal of Sciences)
Since the beginning of the Industrial Revolution, the linear model of economic development has been applied worldwide. Today, this model is heavily criticized for a variety of reasons: from rising commodity prices due to their depletion to more significant economic problems such as the need to protect the environment and the increasing energy demand. After a number of scientific discussions and studies, the concept of the "circular economy" underlying the regenerative approach of production is needed. Circular economy is realized through a variety of measures, activities and approaches, depending on the characteristics of the region and / or the sector, as a result of which regional and business models are typified. The purpose of this report is to analyze the existing and potential regional and business models of the circular economy in the context of sustainable development. Different empirical approaches have been used to find innovative solutions for assessing the models of the circular economy in Bulgaria, including agriculture. The resulting summaries are the basis for proposing new ecological initiatives and measures.